2022
DOI: 10.1186/s40364-022-00435-8
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation-related blood biomarkers show promise for early diagnostics of neurodegeneration

Abstract: Background The strongest risk factor of neurodegenerative diseases (NDDs) is aging. Spontaneous asparaginyl deamidation leading to formation of isoaspartate (isoAsp) has been correlated with protein aggregation in NDDs. Methods Two cohorts consisting of 140 subjects were studied. Cohort 1 contained patients with AD and healthy controls, while Cohort 2 recruited subjects with mild cognitive impairment (MCI), vascular dementia (VaD), frontotemporal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It has been hypothesized that a bottleneck in this clearance process, resulting in accumulation of deamidated proteins in blood, can trigger neurodegeneration. This hypothesis has been strengthened in the recent studies [20,27] in which the IgG levels of antibodies against aHSA were found to be significantly reduced in patients with AD, MCI and VaD compared to healthy donors.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It has been hypothesized that a bottleneck in this clearance process, resulting in accumulation of deamidated proteins in blood, can trigger neurodegeneration. This hypothesis has been strengthened in the recent studies [20,27] in which the IgG levels of antibodies against aHSA were found to be significantly reduced in patients with AD, MCI and VaD compared to healthy donors.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we have shown that Fc-glycosylation patterns of pAbs of AD patients differ from those in healthy controls with a lower abundance of complex galactosylated and sialylated forms in AD [20]. Now we investigated whether the IgG Fc-glycosylation pattern would be different between pAbs enriched against fHSA and aHSA.…”
Section: Fc-glycosylation Patternsmentioning
confidence: 95%
See 2 more Smart Citations
“…As a result, patients with neurodegenerative diseases (NDDs), including AD, had higher levels of isoAsp in their serum albumin. 11 This provides the foundation of an additional diagnostic technique for the early detection of NDDs. Therefore, future studies should employ a multimodal strategy that combines the SOBA technique with deamidation biomarker analysis, which can significantly improve the reliability and sensitivity of this strategy for early detection in at-risk or asymptomatic individuals.…”
mentioning
confidence: 99%